2012
DOI: 10.1002/ajmg.b.32042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Reelin signaling cascade (Ligands–Receptors–Adaptor Complex) on cognition in schizophrenia

Abstract: Our previous neurocognitive studies of schizophrenia outlined two clusters of affected subjects--cognitively spared (CS) and cognitive deficit (CD), the latter's characteristics pointing to developmental origins and impaired synaptic plasticity. Here we investigate the contribution of polymorphisms in major regulators of these processes to susceptibility to schizophrenia and to CD in patients. We examine variation in genes encoding proteins at the gateway of Reelin signaling: ligands RELN and APOE, their commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…A separate study, however, found that RELN SNP rs7341475 was not associated with deficits in working memory, Reelin mRNA expression in brain, or brain structure (Tost et al 2010). Finally, a recent study found significant associations between SNPs of APOE, APOER2, VLDLR, and DAB1 with cognitive performance of subjects with schizophrenia while there was no such association for RELN (Verbrugghe et al 2012). Additionally, in a second cohort of normal aging males, the authors found associations between SNPs of APOE and APOER2 with memory performance.…”
Section: The Role Of Reelin In Schizophreniamentioning
confidence: 94%
“…A separate study, however, found that RELN SNP rs7341475 was not associated with deficits in working memory, Reelin mRNA expression in brain, or brain structure (Tost et al 2010). Finally, a recent study found significant associations between SNPs of APOE, APOER2, VLDLR, and DAB1 with cognitive performance of subjects with schizophrenia while there was no such association for RELN (Verbrugghe et al 2012). Additionally, in a second cohort of normal aging males, the authors found associations between SNPs of APOE and APOER2 with memory performance.…”
Section: The Role Of Reelin In Schizophreniamentioning
confidence: 94%
“…This gene exerted the most significant signal in haploPS (P unadjusted = 6.92E-09; P adjusted = 0.0007) and F ST (P = 2.43E-08), and it plays a central role in the brain development and normal cognitive function (Li et al 2013;Verbrugghe et al 2012). Interestingly, animal study suggested that this gene may play a protective role against cerebral malaria (Delahaye et al 2007), however, it has not been reported in human study.…”
Section: Population Structure Inferencementioning
confidence: 99%
“…The involvement of altered Apo levels in decreased cognitive performance or cognitive decline has been proposed previously (Dassati et al, 2014;Elliott et al, 2010;Huang & Mahley, 2014;La et al, 2007), but has not yet been thoroughly investigated in SZ or BD. A study by Verbrugghe et al (Verbrugghe et al, 2012) conducted an association analysis between disease outcome and cognitive performance in SZ. They described that ApoE, ApoER2, VLDLR, and DAB1 SNPs were significantly related to disease outcome, pre-morbid intelligence and verbal memory.…”
Section: Discussionmentioning
confidence: 99%
“…However, this link between cognitive impairments and Apo levels has not been done for SZ or BD, so far. A study by Verbrugghe and colleagues conducted and replicated a genetic association analysis between disease outcome and cognitive performance in SZ (Verbrugghe et al, 2012). They reported that ApoE, ApoER2, very-low-density-lipoprotein receptor (VLDLR) and disabled-1 (DAB1) single nucleotide polymorphisms (SNPs) were significantly associated with disease outcome, pre-morbid intelligence and verbal memory.…”
Section: Introductionmentioning
confidence: 99%